6.5k views
1 vote
Please help thanks !!!!

Please help thanks !!!!-example-1
User Naman
by
4.6k points

2 Answers

0 votes

Answer:

x = - 11

Explanation:

Given

6(x - 1) = - 72 ← divide both sides by 6

x - 1 = - 12 ( add 1 to both sides )

x = - 11

User Britni
by
4.7k points
6 votes

Answer:

x = -11

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

6(x - 1) = -72

Step 2: Solve for x

  1. Divide 6 on both sides: x - 1 = -12
  2. Add 1 to both sides: x = -11

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 6(-11 - 1) = -72
  2. Subtract: 6(-12) = -72
  3. Multiply: -72 = -72

Here we see that -72 does indeed equal -72.

∴ x = -11 is a solution to the equation.

User Montuno
by
4.4k points